PENGARUH KEPUASAN KERJA LINGKUNGAN KERJA DAN WORK – LIFE BALANCE TERHADAP LOYALITAS KARYAWAN - Larastrini, Putu Meidita; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 8 No 6 (2019), 2019)
Employees are a vital resource for almost all organizations because they are an investment and a source of competitive advantage for businesses and companies. Maintaining competent employees and developing employee loyalty becomes increasingly important and ongoing challenges. This study aims to determine the significant effect of job satisfaction, work environment, and work-life balance on employee loyalty of Puri Raharja General Hospital . The type of data used is qualitative data sourced from respondents' perspective data and hotel overview, and quantitative data is the number of employees of Puri Raharja General Hospital. The number of respondents was 88 employees. Data collection using interview methods and questionnaire methods. The data analysis technique used is multiple linear regression analysis.Based on the results of the analysis found that job satisfaction has a positive and significant effect on employee loyalty, the work environment has a positive and significant effect on employee loyalty, and work-life balance has a positive and significant effect on employee loyalty. The results of this study imply that the more satisfied employees are with their work, the employee loyalty is also high, a good work environment can increase employee loyalty, and good work-life balance implementation can increase employee loyalty   Keywords : Job Satisfaction, Work Environment, Work-Life Balance, Employee Loyalt y